1973
DOI: 10.1136/adc.48.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal convulsions associated with primary disturbance of calcium, phosphorus, and magnesium metabolism.

Abstract: Changes in the concentrations of calcium, phosphorus, and magnesium in the CSF mirrored those in the blood but were less pronounced.Osmolality in blood and CSF was the same in normal and in convulsing infants and there was no difference between these two groups of infants. There are wide differences in the osmolality of breast milk on one hand and most evaporated milk feeds on the other.In terms of associated neurological findings, infants suffering from convulsions due to a primary disturbance of mineral meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
4

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 25 publications
4
32
0
4
Order By: Relevance
“…In the present study we found overall male sex preponderance in neonates who developed seizures which is similar to other studies like Cockburn et al, Fredrichsen, Mc intyre et al and Bagla et al [19][20][21][22] Reason for this sex preponderance is not explainable but may be attributed to some extent to male sex preponderance in our society as male babies are more cared for and immediate medical attention is given to them.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study we found overall male sex preponderance in neonates who developed seizures which is similar to other studies like Cockburn et al, Fredrichsen, Mc intyre et al and Bagla et al [19][20][21][22] Reason for this sex preponderance is not explainable but may be attributed to some extent to male sex preponderance in our society as male babies are more cared for and immediate medical attention is given to them.…”
Section: Discussionsupporting
confidence: 79%
“…Kumar et al 7 in a study showed that primary metabolic disorder accounted for 25% cause of neonatal convulsion. In a study which was carried out over 2 years period on neonatal convulsion by Cockburn et al 9 , it was found that 55% of neonatal convulsions were due to primary disturbances of mineral metabolism. Metabolic cause of convulsion is common in Bangladesh due to delayed and infrequent breast feeding, faulty feeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence in the literature concerning the level of plasma calcium which defines neonatal hypocalcemia 9,10 . Some authors have defined neonatal hypocalcemia as plasma calcium level less than 8 mg/dl 9 , less than 7.5 mg/dl and less than 7 mg/dl 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Electrolyte disturbances are the most common etiology and include hypoglycemia, hypocalcemia, and hypomagnesemia [26]. Hypernatremia and hyponatremia can also produce seizures in the neonatal period but are less common.…”
Section: Seizuresmentioning
confidence: 99%